The Relative Frequency and Risk Factors of Primary Open Angle Glaucoma and Angle Closure Glaucoma - Muhammad Daud Khan, Naila Ali, Syed Ali Wajid, Nasir Saeed (Pakistan Journal of Ophthalmology, 2007)
Purpose: To determine the frequency and compare the potential risk factors for primary open angle glaucoma and primary angle closure glaucoma in admitted patients. Materials And Methods:A detailed history was taken. Patient’s height and mentovertex (MVHt) height was measured in centimeters. Complete ocular examination was carried out, including recording visual acuity, anterior segment examination, posterior segment examination, intraocular pressure measurement, peripheral and central anterior chamber depth, corneal diameter and axial length measurement. Gonioscopy was performed. Visual field was recorded by automated visual field analyzer. Results: One hundred patients were examined, 60 were males and 40 were females. 58 patients had primary open angle glaucoma (POAG), 42 had primary angle closure glaucoma (PACG). Ten patients had systemic associations of hypertension and/ or diabetes mellitus. Mean intraocular pressure was 25.54 mm Hg with no significant difference in gender distribution and with type of glaucoma. No significant difference was found in the height of patient with either type of glaucoma. In POAG the average mentovertex height was 23.52 cm and in PACG it was 20.98cm. Mean axial length of globe in POAG was 23.2mm and in PACG it was 21.3mm. Mean corneal diameter in POAG was 11.29mm and in PACG 11.13 mm. Anterior chamber depth was calculated to be less than 1/4th of corneal thickness in 29%, 1/4-1/2 in 19% and more than1/2 in 52% cases of PACG. It was found significantly shallower in PACG cases than in POAG. Conclusions: We concluded from this study that Primary open angle glaucoma is more common and males are more prone to glaucomatous optic neuropathy. No correlation exists between patient’s height and the type of glaucoma but strong positive correlation is there between the short mentovertex height and angle closure glaucoma. Shorter axial length, smaller corneal diameter and shallower anterior chamber were found to be significant risk factors for angle closure glaucoma.